A magnetic montmorillonite material, preparation method and application thereof

By using magnetic montmorillonite materials as adsorbents, the problem of difficult foam removal during biofermentation is solved, efficient defoaming effect is achieved, and cost and resource waste are reduced through regeneration and recycling.

CN118320781BActive Publication Date: 2025-04-08CHONGQING ACAD OF ANIMAL SCI +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410737551.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-07
Publication Date
2025-04-08
Estimated Expiration
2044-06-07

AI Technical Summary

Technical Problem

The foam generated during biological fermentation is difficult to eliminate, resulting in problems such as loss of fermentation products, strain pollution and environmental pollution. The existing defoaming agents have high prices, waste of resources and adverse effects on the fermentation industry.

Method used

Magnetic montmorillonite material is used as the adsorbent, prepared by step-by-step co-precipitation method, loaded with Fe3O4, has good adsorption and defoaming functions, and can realize desorption and regeneration recycling.

Benefits of technology

The rapid adsorption and separation of active substances in the bio-fermentation broth is achieved, the defoaming effect is significant, and magnetic montmorillonite has good regeneration properties, and can be quickly separated and reused under an external magnetic field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118320781B_ABST
    Figure CN118320781B_ABST
Patent Text Reader

Abstract

The present invention provides a magnetic montmorillonite material, which is loaded with Fe 3 O 4 , the loading capacity is 10-18%. It has good adsorption and defoaming functions for microbial fermentation broth, and can realize desorption and regeneration and recycling. 4. The present invention is particularly suitable for the field of biological fermentation, solving the problem that the existing defoaming agent has poor defoaming effect on biological fermentation broth. At the same time, the present invention is clean, efficient, easy to operate, and low in cost. At the same time, it has good application prospects in industrial production and wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adsorption material, in particular to a magnetic montmorillonite composite material, which can be applied to the field of biological fermentation. Background Art

[0002] Biosurfactants are generally a class of amphiphilic substances with surface activity produced by microorganisms. Aerobic biological fermentation processes are mostly carried out with ventilation. The combination of the introduced air and the surfactants in the fermentation liquid often leads to the formation of foam that is difficult to break, resulting in the loss of fermentation products, strain contamination, sensor contamination, reduced working volume and environmental pollution. Therefore, it is particularly important to eliminate excess foam during the fermentation process.

[0003] At present, the main defoaming methods in industrial production are chemical defoaming, physical defoaming and mechanical defoaming. Among them, chemical defoamers are extremely diverse and highly efficient, so they are most widely used in fermentation production. Mechanical defoamers are also widely used in the food fermentation industry due to their advantages such as being green, non-toxic and conducive to production. In terms of future development prospects, chemical defoamers will gradually lose their hot research status because of their high prices, waste of resources, and many adverse effects on the fermentation industry. With the increasing awareness of green environmental protection, energy conservation and emission reduction, it is urgent to research and develop a clean and efficient defoaming method.

[0004] Natural clay mineral materials are often used as adsorption materials due to their special layered structure, surface adsorption, ion exchange performance, environmental friendliness and low cost. However, clay mineral materials in general applications are in powder form, and it is difficult to separate them from waste liquid after use. Summary of the invention

[0005] The invention provides a magnetic montmorillonite material, which has good adsorption and defoaming functions for fermentation liquid and can realize desorption and regeneration and recycling.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] An adsorption material for biological fermentation, the material is a montmorillonite magnetic material.

[0008] Preferably, the material is loaded with Fe3O4 in an amount of 10 to 18%.

[0009] The above-mentioned adsorption material can be used in biological fermentation production as a defoaming agent to adsorb various active substances such as surface active proteins and polypeptides produced during fermentation. Brevibacillus laterosporus M811 (deposited in China Center for Type Culture Collection, deposit number CCTCC NO: M 2024715) was fermented. Brevibacillus laterosporus Effective adsorption and desorption of active substances produced by metabolism in M811 fermentation broth. Deposit date: 2024.4.18, deposit address: Wuhan University, Wuhan, China.

[0010] In order to reduce the loading rate of Fe3O4 in the magnetic material and increase the adsorption amount, the present invention uses a step-by-step co-precipitation method without the need for N2 protection. The preparation method of the adsorption material is a step-by-step co-precipitation method, which includes preparing Fe3O4, mixing montmorillonite and Fe3O4, magnetic separation, drying, and grinding.

[0011] Specifically, the above method comprises the following steps:

[0012] Step 1: Weigh 3.24 g of ferric chloride hexahydrate and 2.5 g of ferrous sulfate heptahydrate using an electronic balance, add them into a conical flask containing 150 mL of deionized water, and stir at room temperature for 10 min;

[0013] Step 2: Under mechanical stirring, adjust the pH of the solution to 10.0 with 0.5 M NaOH solution, place the reaction bottle in a 70 °C water bath, and continue stirring the reaction for 30 min;

[0014] Step 3: Weigh 13.0 g of montmorillonite and add it to the suspension, stir vigorously for 90 min, and then place it in a 50°C water bath for 60 min to obtain a gray-black mixture with a Fe3O4 loading of 10-18%;

[0015] Step 4: The obtained black solid is washed with distilled water and ethanol for several times, magnetically separated, dried by vacuum rotary evaporation at 60°C, and then ground and passed through a 100-mesh sieve to obtain magnetic montmorillonite.

[0016] The present invention also provides a defoamer regeneration method, the specific steps are as follows:

[0017] Step 1: Pipette 5 mL of 1.0 mmol / L active substance solution into a 10 mL centrifuge tube.

[0018] Step 2: Add 10 mg of magnetic montmorillonite, and centrifuge at 8000 rpm for 15 min after adsorption.

[0019] Step 3: The precipitate was quickly treated with 5 mL of 0.06 M NaOH solution for 1-2 min and then centrifuged. The pH of the supernatant was adjusted to 2.0.

[0020] Step 4: After centrifugation, take the supernatant for liquid phase detection to obtain the desorption rate.

[0021] Step 5: The precipitate is washed with ultrapure water several times until it becomes neutral and can be adsorbed next time.

[0022] The present invention provides a screening method for screening suitable adsorption materials for Brevibacillus laterite The adsorption of M811 metabolically active substances includes the following steps:

[0023] Step 1: Pipette 5 mL of active substance solution with concentrations of 0.01, 0.02, 0.04, 0.05, 0.06, 0.08, 0.1, 0.12, 0.15, 0.2, 0.25, 0.3, 0.5, 0.8, 1.0, 1.2, 1.5, and 2.0 mmol / L into 10 mL centrifuge tubes.

[0024] Step 2: Add 10 mg of adsorption material (rice husk powder, nano-SiO2, nano-TiO2, polystyrene resin, bentonite, talc, kaolin, zeolite, sepiolite, diatomaceous earth, vermiculite, palm powder, activated carbon, magnetic activated carbon, attapulgite, aluminum-pillared montmorillonite and montmorillonite, etc.), and oscillate in a constant temperature oscillating box at 37°C for 15 hours.

[0025] Step 3: Centrifuge and take the supernatant, and determine the concentration of residual active substances by HPLC. Beneficial Effects

[0026] The material provided by the present invention is used as an excellent adsorbent in Brevibacillus laterosporus In the fermentation production of M811, it can achieve the rapid adsorption of active substances in the fermentation liquid and the rapid separation under the external magnetic field to achieve the defoaming effect. It also helps to increase the expression of its active substances.

[0027] The magnetic montmorillonite material provided by the present invention has good regeneration performance. After being quickly treated with a 0.06M NaOH solution, its desorption rate can be close to 100%. The magnetic carrier technology of the present invention combines the magnetic advantage of the magnetic particles Fe3O4 with the high adsorption capacity of the clay material, so that the modified magnetic adsorbent not only has no weakening of adsorption performance, but also can realize the rapid separation of the adsorbent and the adsorbate solution under the action of an external magnetic field. This has great theoretical value and application value for the development of a modification method for natural clay materials and for the treatment of actual wastewater for biological fermentation and production and life.

[0028] The invention uses montmorillonite as raw material and uses a coprecipitation method to perform magnetic modification on the raw material to obtain magnetic montmorillonite. The preparation method is simple, reliable and easy for industrial production.

[0029] The invention can solve the problems that the defoaming agent in the prior art cannot simultaneously meet the requirements of cleanliness, high efficiency, easy operation and low cost, and can be applied to the field of biological fermentation, and also has good application prospects in industrial production and wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Fig.1 Isothermal adsorption curves of active substances on different materials

[0031] Figure 2 Magnetic montmorillonite Brevibacillus laterosporus Effect of M811 on the expression of metabolically active substances

[0032] Figure 3 Comparison of magnetic montmorillonite adsorbing metabolically active substances for 20 minutes and non-adsorbing (left side is the adsorption group, right side is the non-adsorption group)

[0033] Figure 4 Comparison of magnetic montmorillonite adsorbing metabolically active substances for 2 hours and without adsorption (left side is adsorption group, right side is non-adsorption group)

[0034] Figure 5 Comparison of magnetic montmorillonite adsorbed metabolically active substances for 24 hours and non-adsorbed (left side is adsorbed group, right side is non-adsorbed group)

[0035] Figure 6 Product comparison of magnetic montmorillonite (black) and montmorillonite (white) DETAILED DESCRIPTION

[0036] The present invention will be further described below by way of embodiments in conjunction with the accompanying drawings:

[0037] Example 1: Screening of adsorbent materials for Brevibacillus laterosporus Adsorption of metabolically active substances of M811

[0038] preparation Brevibacillus laterosporus M811 metabolically active substances: Brevibacillus laterite M811 was inoculated in NB solid culture dishes for activation and cultured at 30°C and 220 rpm for 15 h, then inoculated into sterilized NB culture medium shake flasks and cultured at 30°C and 220 rpm for 15 h to obtain seed solution. The seed solution was inoculated into an optimized self-made liquid culture medium (15 g / L corn syrup powder, 8 g / L sucrose, 5 g / L ammonium sulfate, 0.3 g / L magnesium sulfate, adjusted to pH 6.9 and sterilized at 120°C for 20 min) at a volume ratio of 4% and cultured overnight at 30°C and 220 rpm to obtain Brevibacillus laterosporus M811 metabolic active substances (mainly composed of the immunomodulatory octapeptide produced by it). The fermentation broth is centrifuged to obtain the supernatant, which is then freeze-dried to obtain freeze-dried powder.

[0039] Will Brevibacillus laterosporus M811 metabolically active substances (mainly composed of the immunomodulatory octapeptide produced by it) were used as targets to understand the adsorption effects of different adsorption materials on them.

[0040] 5 mL of active substance solution with concentrations of 0.01, 0.02, 0.04, 0.05, 0.06, 0.08, 0.1, 0.12, 0.15, 0.2, 0.25, 0.3, 0.5, 0.8, 1.0, 1.2, 1.5, and 2.0 mmol / L were respectively transferred into 10 mL centrifuge tubes, and 10 mg of adsorption material was added, including rice husk powder, nano-SiO2, nano-TiO2, polystyrene resin, bentonite, talc, kaolin, zeolite, sepiolite, diatomaceous earth, vermiculite, palm powder, activated carbon, magnetic activated carbon, attapulgite, aluminum-pillared montmorillonite and montmorillonite. Montmorillonite was purchased from Aladdin (product number F2008085), and the rest were purchased from McLean. After shaking in a constant temperature shaking box at 37°C for 15 h, the supernatant was centrifuged and the concentration of residual active substances was determined by HPLC. Active material adsorption capacity Q e The calculation formula is as follows:

[0041] Q e = (C0-C eq )*V / m

[0042] Where Q e is the amount of active substance adsorbed per gram of adsorbent, mg / g; C0 is the initial concentration of the sample, mg / L; C eq is the residual concentration (equilibrium concentration) of the sample after adsorption, mg / L; V is the volume of the added sample, L; m is the amount of adsorbent, g. eq and Q e are the X and Y axes respectively, and the isotherm adsorption curve is obtained.

[0043]

[0044] The adsorption capacity of rice husk powder, nano-SiO2, nano-TiO2, polystyrene resin, bentonite, talc, kaolin, zeolite, sepiolite, diatomaceous earth and vermiculite is lower than 20 mg / g. The adsorption capacity results of the other five materials are shown in Table 1. The adsorption isotherms of magnetic activated carbon, attapulgite and montmorillonite with higher adsorption capacity are shown in Table 1. Figure 1 The results show that montmorillonite has Brevibacillus laterite M811 had the best adsorption effect on metabolically active substances.

[0045] Example 2: Preparation of magnetic montmorillonite and its adsorption properties

[0046] So far, the main methods for preparing Fe3O4 magnetic nanoparticles are: coprecipitation, microemulsion, thermal decomposition, hydrothermal, sol-gel, biosynthesis, etc. The chemical precipitation method is the preferred method for easy operation, low cost and large-scale preparation of nanoparticles. The more common preparation method of coprecipitation is a one-step method, which is to evenly disperse montmorillonite into a liquid containing Fe2+ and Fe 3+ Then, a certain concentration of ammonia solution or sodium hydroxide solution is added dropwise to the mixed solution, stirred for a period of time and allowed to stand for aging. This process is through the precipitation reaction Fe 2+ +2Fe 3+ +8OH - →Fe3O4+4H2O produces ferroferric oxide Fe3O4, which is loaded on the surface of montmorillonite or enters the interlayer gap of montmorillonite, thus obtaining magnetic montmorillonite. This method is only suitable for the case where the Fe3O4 loading rate is higher than 24%, otherwise non-magnetic α-Fe2O3 will be generated during the reaction; although N2 can be passed into the reaction system to improve this situation, the final product contains some γ-Fe2O3 with weaker magnetism, and the Fe3O4 or γ-Fe2O3 loading rate is higher than 17%.

[0047] In order to reduce the loading rate of Fe3O4 in magnetic materials (increase the adsorption amount), a method for preparing magnetic montmorillonite by step-by-step coprecipitation method without N2 protection was studied. The specific steps of the present invention are as follows:

[0048] Step 1: Weigh 3.2400 g of ferric chloride hexahydrate and 2.5000 g of ferrous sulfate heptahydrate using an electronic balance, add them into a conical flask containing 150 mL of deionized water, and stir at room temperature for 10 min;

[0049] Step 2: Under mechanical stirring, adjust the pH of the solution to 10.0 with 0.5 M NaOH solution, place the reaction bottle in a 70 °C water bath, and continue stirring the reaction for 30 min;

[0050] Step 3: Weigh different amounts of montmorillonite (5.0, 7.0, 9.0, 11.0, 13.0 g, the total mass remains unchanged, and the Fe3O4 loadings corresponding to the Fe3O4:montmorillonite mass ratios are 24.5%, 20.4%, 15.8%, 12.8%, 11.4%, respectively) and add them to the suspension, stir vigorously for 90 min, and then stand in a 50°C water bath for aging for 60 min to obtain a gray-black mixture;

[0051] Step 4: Wash the obtained black solid with distilled water and anhydrous ethanol for several times, separate magnetically, dry by vacuum rotary evaporation at 60°C, grind, and pass through a 100-mesh sieve to obtain magnetic montmorillonite.

[0052] Step 5: The obtained montmorillonite with different loadings is subjected to an adsorption test, and the steps are the same as those in Example 1.

[0053]

[0054] The results are shown in Table 2. It is found that Fe3O4 alone has no adsorption capacity for active substances, and the adsorption capacity of magnetic montmorillonite for active substances is inversely proportional to the Fe3O4 loading. The adsorption capacity of magnetic montmorillonite with a Fe3O4 loading of 11.4% is equivalent to 86.7% of montmorillonite. Although the Fe3O4 loading can be further reduced, its magnetism will be weakened and insufficient to be adsorbed by the magnet and regenerated. Therefore, 11.4% is the optimal Fe3O4 loading condition.

[0055] Montmorillonite Brevibacillus laterosporus Effect of the expression of metabolically active substances in M811: Brevibacillus laterosporus M811 was inoculated into a sterilized LB liquid medium shake flask (15mL / 100mL), and 0, 5, 10, and 15 mg of magnetic montmorillonite (corresponding to a Fe3O4 loading of 11.4%) were added, respectively, and inoculated into the LB medium at a volume ratio of 4%. After culturing at 30°C and 220 rpm for 48 hours, the content was detected by HPLC. The results are shown in Figure 2 As shown. It not only has no adverse effects on the biological fermentation process, fermentation bacteria, and fermentation effect, but also can increase the expression of metabolically active substances. When the amount of magnetic montmorillonite added is 10 mg, the increase in the expression of metabolically active substances is the largest, reaching 23.68%.

[0056] Example 3 Effects of different salt ion solutions, temperatures and pH values ​​on desorption

[0057] 1. Effect of different salt ion solutions on desorption

[0058] Example 2 (Fe3O4 loading 11.4% group) After adsorption, 5 mL of different physiological salt ion solutions (sodium acetate, sodium chloride, sodium nitrate, calcium chloride, magnesium chloride, manganese sulfate, sodium phosphate, ammonium chloride, sodium sulfate, zinc sulfate, ferrous sulfate, aluminum chloride, ferric sulfate) were added to the centrifuged precipitate, shaken at 25°C for 7 hours, and centrifuged at 8000 rpm for 15 minutes. The supernatant was subjected to liquid phase detection to obtain the desorption rate under different conditions, and the formula is as follows:

[0059] Desorption rate (%) = ( C i - C f ) / C i *100%

[0060]

[0061] The results show that the desorption rates of sodium acetate, sodium chloride, sodium nitrate, calcium chloride, magnesium chloride, manganese sulfate, sodium phosphate, ammonium chloride, sodium sulfate and zinc sulfate are all lower than 10%, and the results of ferrous sulfate, aluminum chloride and ferric sulfate are shown in Table 3. This shows that the desorption rate is the highest in ferric sulfate solution.

[0062] 2. Effect of different temperatures on desorption

[0063] Example 2 (Fe3O4 loading 11.4%), after adsorption, 5 mL of ferric sulfate solution was added to the centrifuged precipitate, and the mixture was shaken at 18°C, 25°C, 37°C, and 80°C for 7 h, and centrifuged at 8000 rpm for 15 min. The supernatant was subjected to liquid phase detection to obtain the desorption rate under different conditions.

[0064] The results showed that the desorption rate was the highest under shaking conditions at 18°C.

[0065] 3. Effect of different pH values ​​on desorption

[0066] Example 2 (Fe3O4 loading 11.4%), after adsorption, the precipitation after centrifugation was adjusted to pH (1.0, 2.5, 4.0, 5.5, 7.0, 8.5, 10.0, 11.5 and 12.6) with hydrochloric acid and sodium hydroxide. Centrifuge at 8000 rpm for 15 min, and perform liquid phase detection on the supernatant to obtain the desorption rate at different pH values.

[0067]

[0068] The results are shown in Table 5. When the pH is 1.0, the maximum desorption rate is 40%, and when the pH is 12.5 (the concentration of sodium hydroxide is 0.06 M), the desorption rate can reach 100%.

[0069] Example 4 Evaluation of the adsorption and regeneration capabilities of montmorillonite and magnetic montmorillonite for active substances

[0070] Fermentation metabolic active substances (mainly immune-regulating octapeptides produced by itself) pure product (preparation Brevibacillus laterosporus M811 metabolically active substances (same as in Example 1) were fully dissolved in ultrapure water and centrifuged to obtain a supernatant (1.0 mmol / L). 5 mL was transferred to a 10 mL centrifuge tube, and then 10.0 mg (10.0 ± 0.1 mg) of montmorillonite and magnetic montmorillonite (Fe3O4 loading of 11.4%) were added respectively. 37°C, shaken for 18 hours. The supernatant after centrifugation was detected by liquid phase to obtain its adsorption amount; the precipitate was quickly treated with 0.06M NaOH solution, the supernatant was adjusted to pH 2.0, and the supernatant after centrifugation was detected by liquid phase to obtain the desorption rate; the precipitate was washed with ultrapure water several times until neutral, and then the next adsorption and desorption test was carried out, and the results are shown in Table 6.

[0071]

[0072] It can be seen from Table 6 that the desorption rate of magnetic montmorillonite (Fe3O4 loading of 11.4%) increases with the increase of regeneration times, while the desorption rate of montmorillonite decreases with the increase of regeneration times, indicating that the regeneration ability of magnetic montmorillonite is better than that of montmorillonite. In addition, when the adsorbent is excessive (the active substance is completely adsorbed), the desorption rate of magnetic montmorillonite can be close to 100%.

Claims

1. An application of an adsorption material for Bacillus fermentation as a defoamer, wherein the material is a montmorillonite magnetic material; the material is loaded with Fe3O4, and the loading amount is 10-18%; The preparation method of the adsorption material is a step-by-step co-precipitation method, including preparing Fe3O4, mixing montmorillonite and Fe3O4, magnetic separation, drying, and grinding; The bacillus is Brevibacillus laterosporus with a preservation number of CCTCC NO: M 2024715.

2. The use of the adsorbent material for bacillus fermentation as claimed in claim 1 as a defoamer, wherein the preparation method of the adsorbent material comprises the following steps: Step 1: Weigh ferric chloride hexahydrate and ferrous sulfate heptahydrate, dissolve them in deionized water, and stir at room temperature for about 10 min; Step 2: Adjust the pH of the solution to 10.0 with NaOH solution, place in a 70°C water bath, and continue stirring the reaction for about 30 minutes; Step 3: weigh montmorillonite and add it to the suspension obtained in step 2, stir vigorously for about 90 minutes, and then place it in a water bath at about 50°C for about 60 minutes to obtain a gray-black mixture with a Fe3O4 loading of 10-18%; Step 4: The obtained black solid was washed with distilled water and ethanol, magnetically separated, dried by vacuum rotary evaporation at about 60°C, then ground and passed through a 100-mesh sieve.

3. The use of the adsorbent material for Bacillus fermentation as claimed in claim 1 as a defoamer, wherein the regeneration method of the adsorbent material comprises the following steps: Step 1: Prepare the fermentation liquid to be adsorbed; Step 2: adding the adsorption material, and centrifuging at about 8000 rpm for about 15 minutes after adsorption; Step 3: Adjust the pH of the supernatant to about 2.0 with NaOH solution and centrifuge after 1-2 minutes; Step 4: After centrifugation, the supernatant was taken for liquid phase detection to evaluate the desorption rate; Step 5: The precipitate is washed with ultrapure water several times until it becomes neutral and then used for the next adsorption.

Citation Information

Patent Citations

  • Method for cleanly and efficiently producing microorganism bactericide

    CN102212476A

  • Preparation method of adsorbent of phenolic compound in water

    CN104437409A